Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/jm500807e
|View full text |Cite
|
Sign up to set email alerts
|

CB2-Selective Cannabinoid Receptor Ligands: Synthesis, Pharmacological Evaluation, and Molecular Modeling Investigation of 1,8-Naphthyridin-2(1H)-one-3-carboxamides

Abstract: We have recently identified 1,8-naphthyridin-2(1H)-one-3-carboxamide as a new scaffold very suitable for the development of new CB2 receptor potent and selective ligands. In this paper we describe a number of additional derivatives in which the same central scaffold has been variously functionalized in position 1 or 6. All new compounds showed high selectivity and affinity in the nanomolar range for the CB2 receptor. Furthermore, we found that their functional activity is controlled by the presence of the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
104
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(114 citation statements)
references
References 40 publications
8
104
1
Order By: Relevance
“…[24] In the current study,G lide docking studies revealed that the novel pyridazinones reported hereb ind in as imilar orientation as the 1,8-naphthyridin-2(1H)-one-3-carboxamides. [24] W6.48 is therefore considered to be part of the "toggle switch"f or activation.A s illustrated in Figure 4B,t he 4-chloro-3-methylphenyl pyridazinone substituent of 22 points towardT MH5 and extends deep enoughi nt he binding pocket to block the movement of W6.48(258) and therefore keep its c1a tg+ .T his is consistent with 22 acting as an inverse agonist at the CB 2 R. Therefore, this docking study provides ar ational structural explanation for the ability of ligandss uch as 22 to preventG -protein-de-pendentCB 2 Ra ctivation. [23][24][25][26] This homology model wasp re-equilibrated in as tearoyl-docosahexaenoylphosphatidylcholine( SDPC) bilayer for 300 ns to allow it to adjust in al ipidic environment [23] (see the Experimental Section).…”
Section: Molecular Modelingmentioning
confidence: 54%
See 4 more Smart Citations
“…[24] In the current study,G lide docking studies revealed that the novel pyridazinones reported hereb ind in as imilar orientation as the 1,8-naphthyridin-2(1H)-one-3-carboxamides. [24] W6.48 is therefore considered to be part of the "toggle switch"f or activation.A s illustrated in Figure 4B,t he 4-chloro-3-methylphenyl pyridazinone substituent of 22 points towardT MH5 and extends deep enoughi nt he binding pocket to block the movement of W6.48(258) and therefore keep its c1a tg+ .T his is consistent with 22 acting as an inverse agonist at the CB 2 R. Therefore, this docking study provides ar ational structural explanation for the ability of ligandss uch as 22 to preventG -protein-de-pendentCB 2 Ra ctivation. [23][24][25][26] This homology model wasp re-equilibrated in as tearoyl-docosahexaenoylphosphatidylcholine( SDPC) bilayer for 300 ns to allow it to adjust in al ipidic environment [23] (see the Experimental Section).…”
Section: Molecular Modelingmentioning
confidence: 54%
“…Further exploration of the 1,8-naphthyridin-2(1H)-one-3-carboxamide scaffold in the CB 2 RRmodel, showedt hat antagonists from this series bind in the TMH2-3-6-7 region with the C6 naphthyridine substituent directly blockingt he W6.48(258) toggle switch. [24] In the current study,G lide docking studies revealed that the novel pyridazinones reported hereb ind in as imilar orientation as the 1,8-naphthyridin-2(1H)-one-3-carboxamides. The most potent and selectiveC B 2 Ri nverse agonist, 22,w as docked in a previously published CB 2 RR -state model.…”
Section: Molecular Modelingmentioning
confidence: 54%
See 3 more Smart Citations